MINIMIZATION OF INSIDER THREATS IN INFORMATION PROTECTION SYSTEMS - KOPYTIN, YURII; KOPYTINA, MARYNA; KORCHYNSKYI, VOLODYMYR; KHALED, ALFAIOMI; BIELOVA, IULIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper provides a comprehensive analysis of the issues of minimizing insider threats in enterprises' information protection systems. The key vectors of threats are identified, which appears as result of insider activities, as well as their impact on the information security of the enterprise. The main channels of information leakage and methods of their neutralization are considered. The external and internal risks of the enterprise are assessed, taking into account the probability of insider attacks and potential financial and reputational losses. The approach to classifying insider threats depending on the level of employee access, motives and methods of unauthorized use information is proposed. Based on comparative analysis of risks, methodology for assessing the effectiveness of implementing cybersecurity measures, taking into account the costs of their support, is proposed. The dependence between the level of investment in information protection systems and the degree of risk reduction is researched. The relevance of the paper is justified by the expediency for companies to conduct regular analysis of modern technologies and tools that can be used for detection, warning and prevention of the insider threats, as well as to conduct continuous monitoring of cyber threats, which are constantly evolving and improving the attack methods. The main objectives of the research are: an overview of various types of insider threats and their impact on the enterprises’ information security; analysis of methods and strategies for minimizing insider threats; development of recommendations for enterprises on the implementation of comprehensive strategy for protecting against insider threats, adapted to changing business conditions. The obtained results can be used to construct an effective information security risk management system, which will ensure the stable development of the enterprise in the conditions of growing cyber threats.
Keywords: insider threats; information security; cybersecurity; risk management; threat minimization; monitoring; information protection; financial losses; cyber threats; security investments; adaptation